Engineering Systems and Networks The Way Ahead for Industrial Engineering and Operations Management - Amorim, Marlene; Ferreira, Carlos; Vieira Junior, Milton; Prado, Carlos (Lecture Notes in Management and Industrial Engineering,, 2017)
This book gathers a selection of the best papers presented at the joint international conference ICIEOM-CIO-IIE 2015, offering recent research on industrial engineering, management and operations from an international and interdisciplinary perspective. It includes contributions from different fields, such as operations research, modeling and simulation, production and service management and logistics, information systems and quality, and as such is of interest to both researchers and practitioners. Reflecting the interconnected nature of today's production systems, characterized by intense flows of goods, information and individuals between companies and nations, it is a valuable resource for anyone wanting an in-depth understanding of the field to guide managerial practice in order to take full advantage of existing opportunities.